Effect of Time-Lapse between Intermediate Restoration and Final Restoration on Survival Rate and Changing of Radiographic Periapical Lesion - Aguilar, Panuroot; Hong, Tanison; Tangthong, Pantharee; Phuvoravan, Chalermkwan; Pinchamnankool, Kriangkrai; Phumpatrakom, Panupat (European Journal of General Dentistry, 2024)
Objective This study aimed to assess the impact of intermediate restoration time-lapse on the survival rate and changes in radiographic periapical lesions of endodontically treated teeth.Materials and Methods The included treatment records and periapical films of 62 patients were divided into two groups based on the time-lapse of intermediate restoration: within 4 months group (≤4 m group) and more than 4 months group (>4 m group).Statistical Analysis Survival analysis was conducted using Kaplan–Meier and log-rank test. The predictive clinical factors were assessed using a Cox regression model and hazard ratio, considering both clinical and radiographic outcomes from the latest recall appointment. Changes in periapical index (PAI) scores on radiographs were evaluated using the Chi-square test. Statistical significance was set at p < 0.05.Results The mean survival rate of endodontically treated teeth was 77.4%. The survival rates of the ≤4 m group and >4 m group were 83.3 and 69.2%, respectively, without statistical significance. None of the clinical factors significantly affected the clinical outcome. However, the >4 m group exhibited significantly worse changes in PAI scores between the final restoration appointment and the latest recall.Conclusion Different time-lapses for intermediate restoration did not significantly affect the survival rate. However, an intermediate restoration time-lapse of more than 4 months tended to result in worse changes in PAI scores.
Keywords: endodontics; intermediate restoration; periapical pathology; radiographic image interpretation; treatment outcome